Health and Work of the Elderly: Subjective Health Measures, Reporting Errors and the Endogenous Relationship between Health and Work - Maarten Lindeboom; Marcel J. M. Kerkhofs (Institute for the Study of Labor (IZA), 2002)
This paper aims to explore the interrelation between health and work decisions of elderly workers, taking the various ways in which health and work can influence each other explicitly into account. For this, two issues are of relevance. Self-assessed health measures are usually at hand in empirical analyses and research indicates that these may be endogenous, state dependent, reporting behaviour. Furthermore, even if an objective health measure is used, it is not likely to be strictly exogenous to labour market status or labour income. Health and labour market variables are correlated because of unobserved individual-specific characteristics (e.g., investments in human capital and health capital) Moreover, one?s labour market status is expected to have a (reverse) causal effect on health. A solution to the ?Health and Retirement Nexus? requires an integrated model for work decisions, health production and health reporting mechanisms. We formulate such a model and estimate it on a longitudinal dataset of Dutch elderly.
Keywords: J14; I12; 330; Retirement; health; endogeneity; state dependent reporting errors; Ältere Arbeitskräfte; Arbeitsangebot; Gesundheit; Schätzung; Niederlande